Efficacy of Push and Pull Strategy against Fall Armyworm Spodoptera frugiperda (J.E. SMITH) In Maize in Bhairahawa, Nepal - Chhetri, Pooja Poudel; Adhikari, Anupama; Bhetwal, Nikku; Paudel, Shishir; Sahani, Hemant Kumar; Pandey, Pushpa; Khanal, Dipak (Journal of the Institute of Agriculture and Animal Science, 2024)
Fall Armyworm (FAW), Spodoptera frugiperda (J.E. Smith), a voracious sporadic pest, had been major problem in maize causing significant yield loss and challenging food security around the world. It was first recorded in Nepal on 9th May, 2019 and is distributed in most part of the maize farming regions. Farming system such as maize-legume intercropping has been reported to reduce Fall Armyworm infestation significantly. The experiment for effective management of Fall Armyworm in maize as push and pull strategy was carried at horticulture farm of Institute of Agriculture and Animal Science, Paklihawa Campus, Bhairahawa. Seven treatments including the control were applied in Randomized Complete Block Design. Maize (var. Rampur Hybrid-10) was the main crop, with Napier (var. Super Napier) used as a border crop. All the treatments were replicated three times. The treatments deployed were: Desmodium Desmodium oojeinese (Roxb) H.Ohashi, cowpea (Sampada), blackgram (U-99), greengram (local var.), common bean (Italy 38), soyabean (local var.) and control. On an average, the research showed that Desmodium had the highest resistance to fall armyworm with lowest leaf damage score (4.90), being superior to Soyabean (5.61), Green gram (5.79), Black gram (5.90), Cowpea (6.45), Common bean (6.85), and Control (7.31). The average number of infested plant and infested leaf were least in plot where Desmodium was intercropped, having the highest yield of 8.86 tons/ha. From this experiment, we concluded that Desmodium was the most effective legume among other treatments. However, crops like soyabean and green gram can also be suggested as a next best alternative for ecofriendly management of fall armyworm.